2019
DOI: 10.1093/rheumatology/kez390
|View full text |Cite
|
Sign up to set email alerts
|

High rate of indeterminate results of the QuantiFERON-TB Gold in-tube test, third generation, in patients with systemic vasculitis

Abstract: Objectives To describe the frequency of QuantiFERON-TB Gold in-tube test® (QFT-GIT) indeterminate results due to no response to phytohaemagglutinin A stimulation in the control tube in vasculitis patients prior to immunosuppressant therapy; and to compare it with other groups of patients. Methods This was a single-centre, retrospective study. Patients and controls were included between 1 January 2008 and 31 December 2015. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Furthermore, our study discovered that low lymphocyte count was associated with QFT-GIT indeterminate results. However, high SLEDAI scores seemed not related with a high proportion of indeterminate results, and this differs from some studies [20][21][22][23][24]. Other previous researches showed that CD4+ T cell count, lymphocyte count, and lymphocyte percentage were influencing factors for the indeterminate results of QFT-GIT in HIV and immunosuppressive people [25,26].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, our study discovered that low lymphocyte count was associated with QFT-GIT indeterminate results. However, high SLEDAI scores seemed not related with a high proportion of indeterminate results, and this differs from some studies [20][21][22][23][24]. Other previous researches showed that CD4+ T cell count, lymphocyte count, and lymphocyte percentage were influencing factors for the indeterminate results of QFT-GIT in HIV and immunosuppressive people [25,26].…”
Section: Discussionmentioning
confidence: 59%
“…Based on these results, two hypotheses are proposed: first, the pattern of the inverse correlation is thought to be due to IFN-gamma producing T cell exhaustion, as shown in our previous study on systemic lupus erythematosus (SLE) (12). Several studies have supported this phenomenon by showing a marked decrease in T-cell responses to phytohemagglutinin A in patients with autoimmune diseases (18,19). Second, the absence of statistical significance of this pattern indirectly indicated that the proportion of IFN-gamma in the pathogenesis of AAV is relatively smaller than that in SLE (8,20).…”
Section: Discussionmentioning
confidence: 81%
“…Several parameters were previously demonstrated to influence the T cell response in the IGRA assay [ [13] , [14] , [15] ]. They included PMN and lymphocyte counts, a defective T cell capacity to respond to PHA stimulation (IGRA-PHA), GC dose, and serum albumin level.…”
Section: Resultsmentioning
confidence: 99%